2004
DOI: 10.3748/wjg.v11.i3.451
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of metallic stents in treatment of esophageal carcinoma

Abstract: AIM:To evaluate the effects of self-expanding metal stents (SEMS) in patients with malignant esophageal obstruction and to analyze their prognosis and complications. METHODS:Seventy-four metallic stents were placed under fluoroscopic guidance in 66 patients with esophageal obstruction secondary to carcinoma, of whom, 6 cases were complicated by fistula. RESULTS:After seventy-two stents were successfully used in 66 cases without any severe complications (technical successful rate was 97%), the dysphagia score i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Our review confirms that SEMS provide a rapid, significant improvement in dysphagia in this cohort of patients ( P < 0.0001, Wilcoxon signed ranks). This is in agreement with a number of previous studies, providing experience with a multitude of different SEMS 10–15 . The length of hospital stay following stent insertion was longer than has been suggested by Homs et al ., 1 although, in a comparison of plastic prothesis and SEMS insertion, Knyrim et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our review confirms that SEMS provide a rapid, significant improvement in dysphagia in this cohort of patients ( P < 0.0001, Wilcoxon signed ranks). This is in agreement with a number of previous studies, providing experience with a multitude of different SEMS 10–15 . The length of hospital stay following stent insertion was longer than has been suggested by Homs et al ., 1 although, in a comparison of plastic prothesis and SEMS insertion, Knyrim et al .…”
Section: Discussionsupporting
confidence: 92%
“…have detailed a 78% 6‐month survival in 66 patients with malignant esophageal obstruction. In this cohort, they have reported an 11% two‐year survival 14 . A possible explanation for the brevity of survival may well be our approach to timing of SEMS insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the use of self‐expandable metallic stents, relief of dysphagia appears just after the process and lasts a long time 14 . It has been shown that self‐expandable metallic stents are superior to plastic stents in their promotion of general quality of life 15 .…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that after this treatment, vasculitis and ischemia of the esophageal tissue occurs, and that the pressure exerted by the stent can produce local necrosis which can increase the rate of complications, such as migration of the stent, perforation, hemorrhage and the fistula formation 3,34,37,41 . On the other hand, stent placement with adjuvant cytoreductive therapy can ensure earlier oral food ingestion, prevent stenosis secondary to the radioactive therapy, and allow RT/CT therapy in patients with tracheo-esophageal fistula.…”
Section: Discussionmentioning
confidence: 99%